LITERATURE REVIEW YANG BERHUBUNGAN DENGAN RHEUMATOID ARTRITIS PADA LANSIA - Daryanti; Budi Widiyanto; Sudirman (Politeknik Kesehatan Kemenkes Sorong, 2020)
ABSTRACTIntroduction: Rheumatoid Arthritis (RA) is an autoimmune disease, characterized by asystematic, chronic inflammatory process. One type of rheumatism that is often seen in old age isrheumatoid arthritis. Objective: this study was to determine the factors that influence rheumatoidarthritis in the elderly based on Literature Review (LitRef). Method: Literature review is takenfrom journal articles published online consisting of Indonesian and English journals. The criteriafor retrieving articles are those that are in accordance with the keywords and published at least2004-2019. Results: LitRef shows that the factors that influence Rheumatoid Aretitis in theelderly are (consumption of drugs, menopause, fractures, age, lifestyle, obesity, heredity,knowledge, alcohol, nutrition)Keywords: Literature revew, Rheumatoid Arthritis, ElderlyABSTRAKPendahuluan : Rheumatoid Artritis (RA) merupakan suatu penyakit autoimun, ditandai denganadanya proses peradangan kronis, bersifat sistematik. Salah satu jenis rematik yang sering tampakpada usia lanjut adalah arthritis rheumatoid. Tujuan : penelitian ini adalah untuk mengetahuifaktor-faktor yang mempengaruhi Remuatoid Artritis pada lansia berdasarkan Literature Review(LitRef). Metode : Literature Review diambil dari artikel jurnal yang dipublikasikan secaraonline yang terdiri dari jurnal bahasa Indonesia dan Bahasa Inggris. Kriteria pengambilan artikeladalah yang sesuai dengan kata kunci dan terbit minimal tahun 2004-2019. Hasil : LitRefmenunjukkan bahwa faktor-faktor yang pempengaruhi Reumatoid Aretitis pada lansia adalah(konsumsi obat-obatan, menopause, fraktur, usia, gaya hidup, obesitas, keturunan, pengetahuan,alkohol, gizi)Kata Kunci: Literatur revew, Reumatoid Artritis, Lansia